The degree of dominance of resistance trait against pathogens in F1 winter wheat - L. Murashko; V. Kyrylenko; O. Humeniuk; Yu. Suddenko; N. Novytska (Наукові доповіді Національного університету біоресурсів і природокористування України)
One of the most effective and at the same time environmentally friendly measures of integrated protection of wheat against diseases is the development of resistant varieties through breeding adapted to specific agroclimatic conditions. The purpose of the present study was the phytopathological evaluation of winter wheat collection samples on artificial infection backgrounds in the field and to determine the dominance of resistance of F₁ hybrids to Puccinia recondita and Tilletia caries. The study was conducted during 2023, 2024 in a selection crop rotation on natural and artificial infection backgrounds and in the laboratory of the winter wheat breeding laboratory of the V.M. Remeslo Myronivka Institute of Wheat of the National Academy of Agrarian Sciences of Ukraine according to generally accepted methods. 189 collection numbers of winter wheat were studied against artificial infectious backgrounds of brown rust and stinking smut. The study found that the varieties protected by resistance genes Arthur 71 (Lr9), McNair 2203 (Lr9), Agrus (Lr19), Century (Lr24+ Lr42), TAM-200 (Lr24+ Lr43), V1275 (Lr19), VR89Bo22 (Lr19) were immune to the pathogen Puccinia recondita; immunity to Tilletia caries was reflected by winter wheat varieties Rada (SVK), Famulus (DEU), SHARK/F4. 105W21 (USA), Reia (UKR), Ekspromt, Erythrospermum 24210, and Line 46 (UKR). When studying the composition of the population of Puccinia recondita, it was found that the average efficiency was shown by genes Lr10, Lr13, Lr25, and Lr34 (gene of age resistance) at the 5-10% degree of damage to the lines. The genes Lr9 and Lr19 stably maintained strong resistance and continued to be highly effective. In terms of resistance to Puccinia recondita, superdominance (heterosis) was found in five (14.72% of the total number of hybrid combinations) hybrid combinations Beres/Blueboy II, Beres/TAM-200, Matuo/TAM-200, Tobarzo/TAM-200, Matuo/Blueboy II. It was noted that the local population of the pathogen Tilletia caries is avirulent or slightly virulent to resistance genes: Bt6, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21. The study of the genetics of resistance to this disease showed that among F1 hybrid combinations, 41.63% showed partial positive dominance (PPD). No overdominance to the pathogen of stinking smut was found